Characterization of Structure and Morphology of Cellulose Lyocell Microfibers Extracted from PAN Matrix - Igor Makarov; Ekaterina Palchikova; Markel Vinogradov; Yaroslav Golubev; Sergey Legkov; Petr Gromovykh; Georgy Makarov; Natalia Arkharova; Denis Karimov; Radmir Gainutdinov (Polysaccharides)
Polymer matrices can be reinforced with cellulose fillers in a variety of geometric shapes. Depending on the morphology of the particles, the volume fraction of the composite additive may decrease, while the values of the elastic modulus may increase. Increasing the length while decreasing the width of the cellulose filler is an intriguing path in the development of composite additives and materials based on it. It is difficult to form thin continuous cellulose fibers, but this can be accomplished via the sea-island composite fiber manufacturing process. The creation of cellulose fibrils in polyacrylonitrile (PAN)/cellulose based systems happens during the spinning of the mixed solution. A selective solvent facilitates the isolation of cellulose fibrils. The structure of the isolated microfibers was investigated using X-ray diffraction, IR spectroscopy, SEM, and AFM. The structure of the resulting cellulose microfibers was compared to bacterial cellulose. It has been shown that composite fibers have a superposition pattern, while cellulose fibrils have a structure different from native cellulose and similar to Lyocell fibers (polymorph II). The crystallite sizes and crystallinity of regenerated cellulose were determined. The identified structural parameters for cellulose fibrils provide strength at the level of industrial hydrated cellulose fibers.